Revisiting regulatory independence: The relationship between the formal and de-facto independence of the Egyptian telecoms regulator. (January 2017) - Badran, Ahmed
Regulatory governance scholars tend to focus on either the formal or de-facto independence of regulatory agencies. Very little attention has been given to linking these two sides together and even less has been said about the relationship between these two aspects. In this paper, the relationship between the formal and de-facto independence of the Egyptian telecoms regulator will be investigated. The aim is to contrast these two aspects of regulatory independence. In addition, the way in which the formal independence is translated by the sector regulator into practice. The paper argues that the formal independence of the Egyptian telecoms regulatory agency is an important but not a sufficient factor to guarantee the de-facto independence of the agency. Empirical data collected from 44 interviews with different stakeholders in the Egyptian telecommunications market is analyzed. Documentary analysis of the telecoms Law and other official policy documents and reports is also considered. The initial findings of the paper show that the telecoms law grants the regulator the ability to act independently from the Ministry and the regulated industry. Nonetheless, this strong legal mandate has not been fully translated into independent practices on the ground in regards to the way the regulatory agency connects with the Ministry of Telecoms and the previous sector incumbent. The paper suggests that the relationship between formal and de-facto independence of telecoms regulators should be carefully considered.